Implementasi PP No 11 Tahun 2021 Tentang BUMDes Dalam Meningkatkan Kesejahteraan Masyarakat Desa Panimbangjaya Kabupaten Pandeglang - Kristina, Iis; Riswanda (Universitas Bojonegoro, 2025)
BUMDes are local economic institutions established to manage village potential and assets to improve the welfare of village communities. PP Number 11 of 2021 provides a stronger legal basis for the establishment, management, and development of BUMDes so that they can become competitive drivers of the local economy. This study aims to examine the implementation of this regulation in improving the welfare of the people in Panimbangjaya Village, Panimbang District, Pandeglang Regency. This research uses a descriptive qualitative approach and refers to the implementation theory by Van Meter and Van Horn, which includes six dimensions: policy standards and objectives, resources, inter-organizational communication, characteristics of implementers, economic, social and political conditions, and the disposition of policy implementers. The results show that the implementation of Government Regulation Number 11 of 2021 has not been optimal. The policy standards and objectives have not been achieved, as most BUMDes programs are not running and their impact is not widely felt by the community. Limited human resources, minimal budget support, weak communication, and lack of local government assistance are the main obstacles. While commitment from the village government and BUMDes management remains, strengthening capacity and providing further assistance are necessary to ensure more effective implementation.